Clinicopathologic Correlations of E-cadherin and Prrx-1 Expression Loss in Hepatocellular Carcinoma - Kijong Yi; Hyunsung Kim; Yumin Chung; Hyein Ahn; Jongmin Sim; Young Chan Wi; Ju Yeon Pyo; Young-Soo Song; Seung Sam Paik; Young-Ha Oh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background Developing predictive markers for hepatocellular carcinoma (HCC) is important, because many patients experience recurrence and metastasis. Epithelial to mesenchymal transition (EMT) is a developmental process that plays an important role during embryogenesis and also during cancer metastasis. Paired-related homeobox protein 1 (Prrx-1) is an EMT inducer that has recently been introduced, and its prognostic significance in HCC is largely unknown. Methods Tissue microarray was constructed using surgically resected primary HCCs from 244 cases. Immunohistochemical staining of E-cadherin and Prrx-1 was performed. The correlation between E-cadherin loss and Prrx-1 expression, as well as other clinicopathologic factors, was evaluated. Results E-cadherin expression was decreased in 96 cases (39.4%). Loss of E-cadherin correlated with a higher recurrence rate (p < .001) but was not correlated with patient's survival. Thirty-two cases (13.3%) showed at least focal nuclear Prrx-1 immunoreactivity while all non-neoplastic livers (n = 22) were negative. Prrx-1 expression was not associated with E-cadherin loss, survival or recurrence rates, pathologic factors, or the Ki-67 labeling index. Twenty tumors that were positive for E-cadherin and Prrx-1 had significantly higher nuclear grades than the rest of the cohort (p = .037). In Cox proportional hazard models, E-cadherin loss and large vessel invasion were independent prognostic factors for shorter disease-free survival. Cirrhosis and high Ki-67 index (> 40%) were independent prognostic factors for shorter overall survival. Conclusions Prrx-1 was expressed in small portions of HCCs but not in normal livers. Additional studies with a large number of Prrx-1-positive cases are required to confirm the results of this study.